2017
DOI: 10.1097/ijg.0000000000000724
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Chamber Angle and Trabecular Meshwork Measurements Made by Fourier-domain Optical Coherence Tomography in Healthy White Children

Abstract: FD-OCT proved useful for the noninvasive measurement of TIA and TM metrics in children. Spherical error was the main determinant of TIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…While an earlier study (Kagemann et al 2010) identified this hypo‐reflective region, shown in our study, as shadow of the TM interface, recent studies using high‐resolution ASOCT (Li et al 2017; Crowell et al 2018) confirm this to be the SC with histopathological corroboration. Fernandez‐Vigo et al (2017) also showed the anatomical variations of SC especially with age in healthy children but did not show a communication between the SC and the anterior chamber. Our finding of this communication of the SC with anterior chamber in eyes of healthy children and in some fellow eyes of PCG patients was accidental, and the study was not designed to evaluate this finding.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While an earlier study (Kagemann et al 2010) identified this hypo‐reflective region, shown in our study, as shadow of the TM interface, recent studies using high‐resolution ASOCT (Li et al 2017; Crowell et al 2018) confirm this to be the SC with histopathological corroboration. Fernandez‐Vigo et al (2017) also showed the anatomical variations of SC especially with age in healthy children but did not show a communication between the SC and the anterior chamber. Our finding of this communication of the SC with anterior chamber in eyes of healthy children and in some fellow eyes of PCG patients was accidental, and the study was not designed to evaluate this finding.…”
Section: Discussionmentioning
confidence: 97%
“…Embryologically, this communication could also be part of the development of the SC which originates as a radial vessel in the optic cup, another observation of Sondermann (1930). Earlier studies on AS OCT have also shown images of such a communication, though the authors did not comment on it (Asrani et al 2008; Hong et al 2013; Fernandez‐Vigo et al 2017). We confirmed this communication in multiple ultrathin (0.5 µm thick) histopathological sections (plastic embedded) which refute this direct communication to be an artefact of ASOCT that may have missed thin strands of TM.…”
Section: Discussionmentioning
confidence: 98%
“…Fernandez et al examined 409 right eyes of 409 children with Fourier‐domain OCT proving Fourier‐domain OCT to be a successful non‐invasive tool for measurement of the trabecular‐iris angle and trabecular meshwork.…”
Section: Other Oct Applications/anterior Segment Octmentioning
confidence: 99%
“…AOD 500 was measured as the perpendicular distance from the trabecular meshwork at 500 lm anterior to the scleral spur, to the anterior iris surface (Fern andez-Vigo et al 2017). The length and area of the TM were also measured: TM length was measured from the hyper-reflective point closest to the scleral spur to the hyper-reflective point closest to Schwalbe's line; TM area was measured by tracing the trapezoidal shape delineated by the hyper-reflective tissue not including the surrounding hypo-reflective arc, or TM interface shadow (Wong et al 2009;Kagemann et al 2010;Fern andez-Vigo et al 2017).…”
Section: Examination Proceduresmentioning
confidence: 99%
“…To date most of these angle studies, especially the larger ones, have been performed in adult Asian populations (Usui et al 2011;Shi et al 2012;Hong et al 2013), and only a few such studies have sought to assess the angle in children (Urbak 1999;Jin et al 2016;Fern andez-Vigo et al 2017;Tandon et al 2017). This lack of literature data also means that the possible effects of several factors such as gender, age, refractive error, angle or TM measurements on the size of the anterior chamber angle and its structures have yet to be addressed.…”
Section: Introductionmentioning
confidence: 99%